TINJAUAN HUKUM ISLAM TERHADAP ZAKAT FITRAH DALAM BENTUK UANG - Joni Zulhendra (Normative Jurnal Ilmiah Hukum, 2017)
Zakat is one form of worship to Allah, it has a very big social aspect. Shari'ah has completely established its provisions; of what property should be zoned up to the target of distribution. With zakat the needs of the ummah can be fulfilled, including poverty eradication. Zakat fitrah is a maliyah ritual performed every year. Zakat fitrah payments generally use rice as a staple food that is commonly consumed by the community. But there are also paying or organizing the management of zakat fitrah with money. If using rice, zakat fitrah is paid 2.5 kg of rice. If using the money, zakat fitrah paid to adjust the price of rice in the market. It is therefore easier for people to earn money than basic food items. Thus, giving zakat in the form of money proved to have provided benefit for the people and this is permissible under Islamic law.